2021
DOI: 10.1177/23333936211021576
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Effects of Cumulative Lifetime Violence in Men: Disruptions in the Capacity to Connect with Others and Finding Ways to Reengage

Abstract: We report qualitative findings of our Men’s Violence Gender and Health Study, a multiple method study using a sequential design in which we explored the mental health manifestations of cumulative lifetime violence in men. Survey results revealed that higher cumulative lifetime violence scores were significantly associated with higher scores on depression, post-traumatic stress disorder, and anxiety in a community sample of men ( n = 685) living in Eastern Canada. To obtain a deeper understanding of men’s score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
0
6
0
1
Order By: Relevance
“…Estos aspectos, han sido demostrados por Park et al, (2021), explicitando cómo la masculinidad en una sociedad puede moldear los pensamientos, las emociones, las reacciones y los comportamientos de las víctimas masculinas y limitar el reconocimiento de este fenómeno. Como bien menciona, Taylor et al, (2021), el impacto de la violencia y la experiencia de los hombre como victimas sugieren que las necesidades de salud mental de los hombres con violencia acumulada a lo largo de la vida contradicen las expectativas de los roles de género de ser estoicos.…”
Section: Discussionunclassified
“…Estos aspectos, han sido demostrados por Park et al, (2021), explicitando cómo la masculinidad en una sociedad puede moldear los pensamientos, las emociones, las reacciones y los comportamientos de las víctimas masculinas y limitar el reconocimiento de este fenómeno. Como bien menciona, Taylor et al, (2021), el impacto de la violencia y la experiencia de los hombre como victimas sugieren que las necesidades de salud mental de los hombres con violencia acumulada a lo largo de la vida contradicen las expectativas de los roles de género de ser estoicos.…”
Section: Discussionunclassified
“…Recognition of men’s possible positions as both victim and perpetrator [ 68 ] is foundational in TVI care for anxiety that focuses on choice, safety, trust, and shared decision-making [ 53 , 54 ]. Such interventions play a role in reducing future violence perpetration by men who address detachment from CLV by exerting power and control in periods of high distress and anxiety to gain self-worth and connect with others [ 28 ]. Thus, it is important for health care providers to consider the impact of both past and ongoing violence on the progression of anxiety, and to resist assumptions that violence is merely a reflection of ‘being a man’.…”
Section: Discussionmentioning
confidence: 99%
“…Among men, perceived mastery or personal control was found to partly mediate the relationship between psychological and physical IPV as target and comorbid anxiety and depressive symptoms among men but social support did not [ 27 ]. Yet, using interview data, Taylor et al [ 28 ] found the main mental health manifestation of CLV among men with anxiety, depression and/or posttraumatic stress disorder (PTSD) was perceived detachment from others fueled by perceptions of gender role expectations to be independent, stoic and self-reliant. Men were found to rectify detachment by attempting to gain self-worth in relationships by connecting with others, an approach that contradicts the prevailing demand to solve problems independently like a “man”.…”
Section: Introductionmentioning
confidence: 99%
“…A greater understanding of gender through men’s suicidal thoughts and behaviors is warranted for context, complexity and meaning-making to understand how they comprehend their mental health and suicidal experiences ( Bantjes & Swartz, 2019 ; Hjelmeland & Knizek, 2010 ; Taylor et al, 2021 ). Qualitative research, with its rich focus on lived experience, enhances ways of knowing the subjective experience of suicide to inform better care models for people at risk of suicide ( Chandler, 2019 ; Feldman et al, 2004 ; Stickley et al, 2022 ; WHO, 2021 ).…”
Section: Introductionmentioning
confidence: 99%